To Hunt or Patrol? Social Composition and Location Mediate Scent Marking Decisions of a Large Carnivore - K. Whitney Hansen; Neil R. Jordan; Megan J. Claase; J. W. McNutt; Alan Wilson; Christopher C. Wilmers (Ecology and Evolution)
ABSTRACT While sociality is known to mediate territorial processes, it is less clear how sociality interacts with environmental features and neighbors' location to influence habitat selection and behavior. Scent marking, a fundamental behavior in maintaining territories, can be utilized by receiving conspecifics to evaluate both encounter risk and competitive ability of the depositing individual or group. African wild dog packs were followed in the field across 2010–2021, where researchers recorded individual behaviors and pack composition, including scent marking behaviors. We combined this historical and unique behavioral dataset with co‐occurring GPS collar data to make inferences on territorial behaviors, sociality, and habitat selection across spatial scales. We performed three analyses to determine (1) the relative probability of scent mark placement, (2) the probability of scent marking, and (3) the trade‐off strategy between scent marking and hunting, as predicted by habitat, neighbors' territories, and pack social composition. Specifically, we used resource selection function frameworks to determine how and whether conspecifics influenced habitat selection and behavior at multiple orders of selection. We found that conspecifics were influential across all three analyses, and mediated the impact of habitat on scent mark placement and probability. Scent mark placement and probability were both influenced by the social composition of packs, specifically pup presence, pack size, and number of overlapping neighbors, while pack size and pack experience influenced territorial maintenance strategy. Our findings demonstrate the importance of social structure across scales of territorial processes, from larger scale habitat selection to the probability of a behavior. We demonstrate how key behavioral theories underpinning territoriality function at the scale of habitat selection and behavioral decision‐making in a free‐ranging, large carnivore. Future research should continue to incorporate sociality in understanding the habitat selection of animals.